1996
DOI: 10.1039/ja9961100643
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric and theoretical investigations into the formation of argon molecular ions in plasma mass spectrometry

Abstract: The a bundance and distribution of argon molecular ions (e.g., ArH', ArO', ArN', Ar,' and MAr'; M = metal) in plasma MS (ICP-MS, LA-ICP-MS and rf-GDMS) were investigated and compared. In ICP-MS the non-metal argon molecular ions were formed with higher intensity compared with the metal argide ions. This could be explained by theoretical calculations of the binding energies. The ArH' ion can be viewed as an isoelectronic system, comparable to HCI. The intensities of diatomic metal argide ions relative to metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 16 publications
2
33
1
Order By: Relevance
“…Response ((c/s)/(mol/dm^3) Differences in the dissociation energies among MAr + ions may be influenced by both the electronegativity of the transition metal and electron configuration of the metal ion. It has been suggested that a more covalent-type interaction occurs between the metal ion and argon neutral for metals with higher electronegativities [17]. While this is a very weak covalent interaction for all transition metals with Ar, it would account for the higher MAr has a more complex ground state electron configuration.…”
Section: Mass Bias Correctionsmentioning
confidence: 97%
“…Response ((c/s)/(mol/dm^3) Differences in the dissociation energies among MAr + ions may be influenced by both the electronegativity of the transition metal and electron configuration of the metal ion. It has been suggested that a more covalent-type interaction occurs between the metal ion and argon neutral for metals with higher electronegativities [17]. While this is a very weak covalent interaction for all transition metals with Ar, it would account for the higher MAr has a more complex ground state electron configuration.…”
Section: Mass Bias Correctionsmentioning
confidence: 97%
“…The relative production of diatomic metal oxides (i.e., MO + /M + ) has been found to correlate with bond strengths (or bond dissociation energies) in studies of molecular ion formation during ICP‐MS analysis (e.g., Michiels and Gijbels 1984, Becker and Dietze 1995, 2000, Becker et al. 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The production of diatomic argides has also been found to correlate with bond strengths (e.g., Barshick et al. 1995, Becker and Dietze 1997), and also with diatomic oxide production in a study of REE molecular ion formation during ICP‐MS analysis, albeit with MAr + /MO + on the order of < 10 −3 (Becker et al. 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the abundance and distribution of argon molecular ions (e.g. ArH + , ArO + , ArN + , Ar 2 + , and MAr + ) were compared for rf-GD-MS, ICP-MS, and laser ablation (LA)-ICP-MS [101]. The highest intensity of metal argide ions was observed in rf-GD-MS.…”
Section: Rf-gd-(double Focusing) Msmentioning
confidence: 99%